ORGANIZATIONAL COMMUNICATIONS - Anggraini, Siti (Universitas Prof. Dr. Moestopo (Beragama), 2007)
To be able to indentify characters of an organization indicative of healthy status.To understand techniques designed to facilitate communications in complex organizational structures